2015
DOI: 10.1177/0959683615596821
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoenvironmental evidence for the impact of the crusades on the local and regional environment of medieval (13th–16th century) northern Latvia, eastern Baltic

Abstract: This paper evaluates the impact of the crusades on the landscape and environment of northern Latvia between the 13th-16th centuries (medieval Livonia). The crusades replaced tribal societies in the eastern Baltic with a religious state (Ordenstaat) run by the military orders and their allies, accompanied by significant social, cultural and economic developments. These changes have previously received little consideration in palaeoenvironmental studies of past land use in the eastern Baltic region, but are fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…The topmost 0.5 m of unconsolidated sediment was sampled using a Willner‐type gravity sampler. Lake Āraišu revealed a 12.4‐m‐long sediment sequence of homogeneous gyttja (Stivrins et al ., ), while an 8‐m‐long sequence of alternating silt and homogeneous gyttja was obtained from Lake Trikātas (Stivrins et al ., ). Both sequences were analysed for pollen, non‐pollen palynomorphs, loss‐on‐ignition and magnetic susceptibility (Stivrins et al ., , 2016).…”
Section: Study Sites and Background Informationmentioning
confidence: 97%
See 1 more Smart Citation
“…The topmost 0.5 m of unconsolidated sediment was sampled using a Willner‐type gravity sampler. Lake Āraišu revealed a 12.4‐m‐long sediment sequence of homogeneous gyttja (Stivrins et al ., ), while an 8‐m‐long sequence of alternating silt and homogeneous gyttja was obtained from Lake Trikātas (Stivrins et al ., ). Both sequences were analysed for pollen, non‐pollen palynomorphs, loss‐on‐ignition and magnetic susceptibility (Stivrins et al ., , 2016).…”
Section: Study Sites and Background Informationmentioning
confidence: 97%
“…The peak in SCP emissions occurred in AD 1982±10 (Latvenergo electric utility company emissions data; Stivrins et al ., ). The age model of the Lake Trikātas sediment sequence was established by six accelerator mass spectrometry (AMS) 14 C dates (Stivrins et al ., ). The chronology of Teiči Bog peat is based on radionuclide dating of 210 Pb, 137 Cs and 241 Am, SCPs and 11 AMS 14 C samples of Sphagnum stems (Supporting Information Tables S1 and S2).…”
Section: Study Sites and Background Informationmentioning
confidence: 99%
“…On the other hand, these changes in forest structure towards a more open character and the presence of macrocharcol could also signal human impact. Evidence of human activity were detected earlier since the Mesolithic in Latvia (Kalnina et al 2004;Stivrins et al 2016), but pollen of cultivars (Secale cereale) in this region were only detected around 1500 cal yr. BP (Stivrins et al 2014). Similarly, the first record of pollen of Secale cereale in NE Poland was around 1500 cal yr. BP (Gałka et al 2014b), which support the interpretation of increased role of humans on the vegetation composition since ca.…”
Section: Discussionmentioning
confidence: 99%
“…Previous palaeobotanical studies (plant macroremains and pollen) of poor fen peatlands in coastal dune areas in the southern Baltic Sea coast in Poland showed that their development was associated with Baltic Sea level changes (Tobolski 1987). In the eastern part of the Baltic coast, high-resolution analyses of plant macroremains have mainly targeted boreal raised bogs (Sillasoo et al 2007(Sillasoo et al , 2011Väliranta et al 2007) and dealt with postglacial palaeoenvironmental changes including tree migration, climatic events, human impact and peat accumulation (Amon et al 2010;Ozola et al 2010;Veski et al 2012;Kalnina et al 2015;Stankevica et al 2015;Stivrins et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Human impact increased gradually along the growing number of population in the surrounding of lakes and their catchment areas. Lake ecosystems became affected by prolonged human economic activity in the Early Metal Age and the Iron Age (Roberts 1998;Kalnina et al 2004;Staškova et al 2013;Brown, Pluskowski 2014;Stivrins et al 2015). During the Medieval Age denudation in the lake catchments areas, erosion and terrestrial material transport and accumulation on lake bottoms were caused by deforestation and agricultural activities (Hoffman 2014).…”
Section: Introductionmentioning
confidence: 99%